A Igreja Católica e o centro Dom vital nos anos de 1950 - Godoy, João Miguel Teixeira de (Revista eclesiástica brasileira, 2018)
The purpose of this text is to reconstitute and analyze some dimensions of the Dom Vital Center trajectory in the 1950s, using the material published by the magazine “The Order”. The main challenges, thematic, initiatives and the central transformations by which the Catholic Church has passed in a decisive context of structural changes in Brazilian society were examined. It was also tried to establish some impacts of the creation of the CNBB in this historical context.